Spine and Hip Range of Motion and Foot Morphology in Adolescent Female Ballet Dancers - Tomasz Rutkowski (Jan Długosz University in Częstochowa, 2022)
The purpose of this study was to assess the spine and hip range of motion and foot angles in adolescent female dancers as compared to those of non-dancing females of the same age. Twenty adolescent female ballet dancers (DANCE) and a control group (CON) of 20 adolescent females were examined. The inclusion criterion for the study group was participation in dance training for over 10 years. Spine and hip range of motion (ROM) assessments were carried out using a goniometer and centimeter tape. Foot angles were assessed using a podoscope. In spinal ROM examination, statistically significant differences were demonstrated in the Tomayer's test, thoracic spine mobility, and lumbar rotation ranges. During foot angles evaluation, statistically significant differences were demonstrated in the Hallux Valgus angle of both feet. Ballet dancers developed greater hallux valgus in both the dominant and non-dominant limbs. They demonstrated higher flexion and extension range of motion in the thoracic spinal segment and the lumbar spine movement for the extension and rotation. The obtained results demonstrate that adolescent ballet dancers are predisposed to an increased risk of pain related to the trauma of the musculoskeletal system.